Incidence of malignancy in non toxic multi-nodular goiter an institutional experience - G. Soomro, A.; R. Surahio, A.; A. Ali, S.; A. Dahri, A.; J. Siddiqui, A. (Scientific Journal of Medical Science, 2014)
The objective of the study is to determine the incidence of malignancy in non toxic multinodular goiter patients who underwent thyroid surgery in our institution. This is a prospective study carried out in the Department of general surgery, Liaquat University of Medical & Health Sciences Hospital Jamshoro, from January 2011 to December 2011. A total no. of 95 cases with clinical diagnosis as non toxic Multinodular goiter who underwent subtotal thyroidectomy were included in the study. Their biopsy specimen were sent to our university laboratory. The biopsy reports were collected in a week time and results were recorded. All the data was recorded on predesigned Performa. Out of 95 patients 7 (7.37%) patients were diagnosed as having malignancy on biopsy reports. Females (6 patients) were affected more commonly then male patients. Papillary carcinoma is the more commonest variant seen in 5 (71.4%) patients, follicular carcinoma in 1(14.3%) patient while Medullary carcinoma is also reported in 1(14.3%) patient. We conclude that the risk of malignancy in non toxic Multinodular Goiter is not to be under estimated, and a dominant nodule in Multinodular Goiter should be valued for thyroid cancer .